Supply Chain Risk Management for the SME’s - Yaakub, Sabariah; Mustafa, Hamidatun Khusna (2015)
Small and Medium Enterprises (SMEs) are a vital component in economic development and bring benefits to the country as they provide employment, increase income, and foster economic growth. However, SMEs have many shortcomings including small size, short capital, and reliance on support from the government. In addition, SMEs are usually companies that are less structured, with small management group, inadequately organised, as well as having informal risk management structure. This study argues for the benefit of adopting SCRM in Malaysian SME. Supply chain risk management (SCRM) focuses on supply chain risk phenomena and provides models for the analysis of several types of supply chain risks that occur in both supply and demand sides of the supply chains. The purpose of SCRM is to recognise the potential supply chain uncertainties and prevent the uncertainties with appropriate action. SCRM is made of four basic categories; risk sources, risk consequences, risk drivers, and risk mitigation strategies. This study focuses on risk mitigation strategies that should be implemented by SME to overcome challenges that they faced. The main problem is that there is lack of knowledge in the application of SCM, especially SCRM in the context of SMEs. In fact, there are still plenty of companies that have not establish a structured supply chain risk management and mitigation system and unaware of supply chain disruption risk management. Therefore, this study seeks to examine risk mitigation strategies and their effect on the company’s performance in Malaysian SME’s. Data was collected through survey questionnaire and the respondents consist of SMEs located in Malaysia. Data analysis was conducted using SPSS and findings indicate that there is significant relationship between risk mitigation strategies adopted by the SMEs and their company performance.